Development of the Technological Scheme of the Combined Frontal Plough and the Justification of the Parameters of Disc Working Bodies - Yesoyan, A. M.; Mikayelyan, G. M.; Karapetyan, A. G. (ՀԱԱՀ հիմնադրամ)
It has been established that there is a need for regular inclusion of soil plowing in the process of minimum tillage. The need for regular inclusion of soil plowing in the process of minimum tillage has been established. A technological scheme for a combined machine has been developed, and a combined front plough for smooth plowing capable of performing both basic and surface soil tillage in a single pass has been proposed. Several geometric, operational, and technological parameters of the proposed plow working body have been determined. The feasibility of using a combined front plough for smooth plowing has been confirmed.
Keywords: Agricultural Engineering